Assessment of gastroprotective activity of aqueous leaf extract of Ageratum conyzoides L.: Role of mucous cells, anti-apoptotic (Bcl-2) and tumor suppressor (p53) proteins - Dayo Rotimi Omotoso; Gerald Ikechi Eze (Shahrekord University of Medical Sciences, 2022)
Introduction: Generally, factors that up-regulate gastric mucosal protective factors or down-regulate aggressive factors contribute to the maintenance of mucosal integrity. This study was done to assess the role of mucous cells, Bcl-2 and p53 proteins during the gastroprotective activity of aqueous extract of Ageratum conyzoides.Methods: The phytochemistry of A. conyzoides extract was analyzed using a gas chromatography-mass spectrometer. Animals were subdivided into five groups, including non-treated normal control group A, non-treated test control group B, and treated groups C-E (Pre-treated with 100, 300, and 500 mg/kg A. conyzoides, respectively for 28 days). After the treatment period, pyloric-ligation was used to induce mucosal injury. Gastric tissues were harvested, grossly examined, and processed for histological, histochemical, and immunohistochemical studies. Stained sections were examined and quantified using image-J software. The data were analyzed using IBM-SPSS (version 23), and comparisons were checked via t test and analysis of variance.Results: Mild mucosal erosion was observed in the treated groups, but intense erosion was prominent in the test control animals. There was an insignificant increase in mucous cells, a significant (P < 0.05) increase in Bcl-2 expression without a significant increase in p53 expression in gastric mucosa of pre-treated animals compared to normal control. Gastric mucosa of test control showed a significant (P < 0.05) decrease in mucous cell count and Bcl-2 expression with a significant concomitant increase in p53 expression.Conclusion: Increased mucous cell population and reciprocal expressions of Bcl-2 and p53 proteins in the gastric mucosa of animals highlighted the sub-cellular mechanisms of gastroprotective activity of A. conyzoides.